Analisis Produksi dan Komoditas Sayuran Unggulan di Kabupaten Rejang Lebong Tahun 2023–2024 - Dewi Stopia Nengsi; Reflis Reflis; Devi Monika Sihite; Rahmawati Rahmawati; Aliyanti Zumrona (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze production levels and identify leading vegetable commodities in Rejang Lebong Regency during the period of 2023–2024. The data used is secondary data sourced from the Rejang Lebong Regency Agriculture Office and empirical calculations based on Location Quotient (LQ) analysis. The results show that the total vegetable production in Rejang Lebong Regency in 2023 reached 3,451,596 quintals and decreased to 3,198,925 quintals in 2024. The commodities with the highest average production were cabbage (647,021 quintals), eggplant (646,994.5 quintals), and carrots (339,041.5 quintals), while the lowest production was found in kale and long beans. LQ analysis shows that there are eight leading commodities (LQ > 1), namely spring onions, green beans, cauliflower, potatoes, cabbage, mustard greens, carrots, and large chilies, most of which are highly competitive highland crops. The results of this study confirm that Rejang Lebong Regency has strong potential as a horticultural center in Bengkulu Province. Therefore, a commodity-based agricultural development strategy is needed that is oriented towards increasing productivity, added value, and the region's competitiveness in a sustainable manner.